Yolk-Shell-Structured Aluminum Phenylphosphonate Microspheres with Anionic Core and Cationic Shell - Zhang, L.; Qian, K.; Wang, X.; Zhang, F.; Shi, X.; Jiang, Y.; Liu, Shaomin; Jaroniec, M.; Liu, Jian (WILEY-BLACKWELL, 2016)
Spherical materials with yolk-shell structure have great potential for a wide range of applications. The main advantage of the yolk-shell geometry is the possibility of introducing different chemical or physical properties within a single particle. Here, a one-step hydrothermal synthesis route for fabricating amphoteric yolk-shell structured aluminum phenylphosphonate microspheres using urea as the precipitant is proposed. The resulting microspheres display 3D sphere-in-sphere architecture with anionic core and cationic shell. The controllable synthesis of aluminum phosphates with various morphologies is also demonstrated. The anionic core and cationic shell of the aluminum phenylphosphonate microspheres provide docking sites for selective adsorption of both cationic methylene blue and anionic binuclear cobalt phthalocyanine ammonium sulphonate. These new adsorbents can be used for simultaneous capture of both cations and anions from a solution, which make them very attractive for various applications such as environmental remediation of contaminated water.